Seed Biopriming Using Plant Growth Promoting Rhizobacteria (PGPR) - Milka Saputri; Linda Advinda; Azwir Anhar; Violita; Moralita Chatri (Jurnal Serambi Biologi, 2023)
Rhizobacteria are bacteria found on the surface of plant roots and are able to increase plant growth known as Plant Growth Promoting Rhizobacteria (PGPR). Rhizobakteri can be used for plant germination by biopriming. Biopriming is hydration of seeds in a controlled manner using biological compounds. Several species of plant growth promoting rhizobacteria that can be used for biopriming are Pseudomonas fluorescens, P. putida and Bacillus subtilis. Biopriming is an alternative method for controlling seeds from soil-borne pathogens and can help farmers use microbes to apply the crops they want. From several research results, biopriming has been proven to increase plant productivity.